Outcome, predictors and longitudinal trajectories of subjects with critical illness polyneuropathy and myopathy (CINAMOPS): study protocol of an observational cohort study in a clinical and post-clinical setting - Bergmann, Jeannine; Egger, Marion; Müller, Friedemann; Jahn, Klaus (BMJ open, 2024)
IntroductionCritical illness polyneuropathy and myopathy (CIP/CIM) are frequent complications in the intensive care unit (ICU) with major consequences for the progress and outcome of subjects. CIP/CIM delays the weaning process, prolongs the hospital stay and increases the mortality rate. Additionally, it may have long-term consequences beyond the hospitalisation phase with prolonged disability. Even though there is growing interest in CIP/CIM, research about the clinical and post-clinical course as well as the middle-term and long-term outcomes of subjects with CIP/CIM is scarce. A large prospective study of critically ill subjects is needed with accurate diagnosis during the acute stage and comprehensive assessment during long-term follow-up.Methods and analysisThis prospective observational cohort study aims to compare the clinical and post-clinical course of chronically critically ill subjects with and without the diagnosis of CIP/CIM and to determine predictors for the middle-term and long-term outcomes of subjects with CIP/CIM. In addition, the influence of the preclinical health status and the preclinical frailty on the long-term outcome of subjects with CIP/CIM will be investigated.This single-centre study will include 250 critically ill patients who were invasively ventilated for at least 5 days at the ICU and show reduced motor strength. At five study visits at admission and discharge to neurological rehabilitation, and 12, 18 and 24 months after disease onset, a comprehensive test battery will be applied including assessments of functioning and impairment, independence, health-related quality of life, activity and participation, cognition, gait and balance, fatigue, mental health and frailty.Secondary objectives are the documentation of therapy goals, therapy content and achieved milestones during the rehabilitation, to evaluate the clinimetric properties of the Mini-BESTest in critically ill patients, and to evaluate the time course and outcome of subjects with CIP/CIM after SARS-CoV-2 infection.Ethics and disseminationThe study was approved by the ethical committee of the Ludwig-Maximilians University Munich. Participants will be included in the study after having signed informed consent.Results will be published in scientific, peer-reviewed journals and at national and international conferences.Trial registration numberGerman Clinical Trial Register (DRKS00021753).